Analisis Produksi Usahatani Padi Sawah (Oryza sativa L) dengan Sistem Tanam Pindah - Fatmawati, Fatmawati; Ismail, Yulan (AGRICOLA, 2022)
This study aims 1) to find out the simultaneous effect of land use (X1), seeds (X2), use of fertilizers (X3), and use of labor (X4) on rice production (Y) at Padengo Village, Dengilo Subdistrict, Pohuwato District, 2) to find out the partial effect of land area (X1), use of seeds (X2), use of fertilizers (X3), use of labor (X4), on rice production (Y) at Padengo Village, Dengilo Subdistrict, Pohuwato District. The total population is 196 lowland rice farmers with a transplanting system. The determination of the sample uses the Slovin formula with 36 farmers taken by using simple random. The data analysis uses multiple regression analysis of the Cobb Douglass' function. The results of the study show that: 1) Simultaneously (in F-test), the variables of land area (X1), seeds (X2), fertilizer (X3), and labor (X4) have a significant effect on rice production (Y) of with a transplanting system at Padengo Village, Dengilo Subdistrict, Pohuwato District. 2) Partially, the variables of the area of land (X1) and fertilizer (X3) have a significant effect on rice production (Y), and the variables consisting of seeds (X2) and labor (X4) have no significant effect on the rice production (Y).